Proposal of a p-type Back-Enhanced Tunnel Field Effect Transistor - Mori, C. A.B.; Agopian, P. G.D. [UNESP]; Martino, J. A. (Institute of Electrical and Electronics Engineers (IEEE), 2019)
In this paper we propose a new p-type Tunnel Field Effect Transistor based on the planar Back-Enhanced structure (BE-pTFET), by removing the p-type drain doping and using a back bias to obtain similar on-state behaviors to those of a conventional pTFET, while eliminating the ambipolar effect.
Keywords: Silicon-On-Insulator (SOI); Tunnel Field Effect Transistor (TFET); Ultra-Thin Body and Buried oxide (UTBB)